2023
DOI: 10.3390/cells12081130
|View full text |Cite
|
Sign up to set email alerts
|

Altered Epigenetic Profiles in the Placenta of Preeclamptic and Intrauterine Growth Restriction Patients

Abstract: Intrauterine growth restriction (IUGR) and preeclampsia (PE) are placental pathologies known to complicate pregnancy and cause neonatal disorders. To date, there is a limited number of studies on the genetic similarity of these conditions. DNA methylation is a heritable epigenetic process that can regulate placental development. Our objective was to identify methylation patterns in placental DNA from normal, PE and IUGR-affected pregnancies. DNA was extracted, and bisulfite was converted, prior to being hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The relative amount of each transcript was calculated using the ΔΔCT method and normalized to the endogenous reference gene beta-actin. The reference gene was chosen based on literature review [ [36] , [37] , [38] , [39] ].…”
Section: Methodsmentioning
confidence: 99%
“…The relative amount of each transcript was calculated using the ΔΔCT method and normalized to the endogenous reference gene beta-actin. The reference gene was chosen based on literature review [ [36] , [37] , [38] , [39] ].…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14] A recent study has revealed the presence of common genes exhibiting differential methylation in both intrauterine growth restriction and preeclampsia, which suggested the genetic similarity between the two conditions. 15 The patterns of DNA methylation in human placenta have been demonstrated to be reliable and significantly associated with fetal growth, which could function as a potential marker for the intrauterine environment and fetal development. [16][17][18] Therefore, placental changes in FGR need a thorough study by the DNA methylation analysis using an efficient detection platform to acquire more information for placental methylome analyses.…”
Section: Introductionmentioning
confidence: 99%